Prospects of Culture, Science and Human in the Context of a Technocratic Tide of the Post-Industrial Era - Antonova, E.L.; Taranova, A.E.; Antonova, E.A. (International Journal of Criminology and Sociology, 2020)
The main aim of the study is to investigate prerequisites, essence and possible consequences of deaxiologisation trends in culture and deanthropologisation tendencies in science which arose out in the post-industrial age. Globalization processes are of a great importance in deprivation the science in its technocratic mechanistic interpretation of its historically determined constructive “human-centric” potential that had been implementing through creation and development of spiritual foundations of a human and society. The new shape of science – techno-science – exists without general metaphysical basis, summarizing and generalizable epistemological principles and person-oriented beginnings. It becomes to signify the return to mechanism in the field of implementation of logical procedures and processes but in the new – technocratic – dimension. The “new” mechanism, unlike the “classic”, is not about reducing the nature of man, society and culture to their nature-centric grounds that base and depend on physical laws, but is about orientating to extrabiological and virtual technical analogies, so it makes one to point out comprehensive competition between the human and artificial intelligence in all fields of vital activity. The main points and conclusions have their grounds on analysis of the most significant stages of science development from classics to post-non-classics.